THE POSITION OF AGRICULTURAL SECTOR IN THE ECONOMY OF SUMENEP REGENCY - akhmad yusup (Agriscience, 2021)
Sumenep is one of the largest agricultural commodity producing areas in Madura, especially food commodities. So that the Agriculture, Forestry, and Fisheries Business Fields become one of the idols in the economy in the Regency. The purpose of the study is to determine the state of the position of the agricultural sector in the economy in the period 2017 to 2019 in the Sumenep Regency area. 2) Knowing the description of the field in Sumenep Regency in the future. The method used in this research is quantitative descriptive analysis with Location Quotient data analysis, and Dynamic Location Quotient. The results of the study show: 1) The existing economic sources in Sumenep Regency in 2015-2019 are agriculture, electricity and gas sector, mining and excavation sector, clean water, business sector, restaurant and hotel, finance, company services and rental. The sub-sector as the basic sub-sector for the economy in Sumenep Regency during 2015-2019 consists of the plantation crop agriculture sub-sector, plantation agriculture sub-sector, food agriculture and search. 2) The economic sector of Sumenep Regency during 2015-2019 which experienced a change in position in the future there were 15 sectors and which did not experience a change in position and remained in the previous position there were two sectors. The sector changed from the basic sector to non-base. The sub-sectors of Sumenep Regency where there will be a change in position in the future during 2015-2019 are agricultural crops, plantation crops and agricultural services from base to non-basic, while horticultural crops and livestock from non-basic.